Central and peripheral circulation differ during off-pump coronary artery bypass grafting - Saemann, Lars; Zubarevich, Alina; Wenzel, Folker; Soethoff, Jasmin; Korkmaz-İçöz, Sevil; Hoorn, Fabio; Karck, Matthias; Simm, Andreas; Szabó, Gábor; Veres, Gábor (Reviews in cardiovascular medicine, 2024)
Background: Off-pump coronary artery bypass grafting (OPCAB) is an alternative to on-pump coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB). During OPCAB, the temporary use of an intracoronary shunt and inotropic medication or catecholamines should keep the central hemodynamics constant. Nevertheless, the need for conversion to on-pump CABG often occurs unexpectedly, most likely due to circulation instability. Circulation instability can appear first in peripheral body parts; therefore, peripheral microcirculation might serve as a predictor for the upcoming conversion to on-pump CABG. We investigated the impact of coronary artery ligation and shunt insertion during OPCAB on cutaneous microcirculation (cLDP) with Laser Doppler Perfusion Technology and transcutaneous oxygen partial pressure (tcpO2). Methods: In a pig model of OPCAB, peripheral circulation was evaluated after cLDP (N = 17) and tcpO2 (N = 6) monitoring. Systolic, diastolic, and mean arterial pressure were also observed to prove the independence of perfusion measurement results from hemodynamic parameters. Results: Ligation time during cLDP and tcpO2 monitoring were 101 ± 49 s and 83 ± 33 s, respectively. Shunt time was 11 ± 3 min during cLDP and 13 ± 2 min during tcpO2 measurement. Ligation of the left anterior descending coronary artery (LAD) reduced cLDP significantly to 88 ± 14% (p = 0.007) and tcpO2 to 71 ± 25% (p = 0.038). Inserting a temporary shunt into the LAD significantly improved cLDP (p = 0.006) and tcpO2 (p = 0.015) compared to ligation. cLDP was restored to 99%, and tcpO2 was restored to 91% of the baseline level before ligation. All hemodynamic parameters remained stable and did not change significantly during OPCAB. Conclusions: Although hemodynamic parameters stayed constant, peripheral microcirculation was influenced markedly during OPCAB. Inserting a temporary shut into the LAD leads to a complete normalization of peripheral microcirculation, regarding evaluation by cLDP and tcpO2.